Assessment of extreme values in geomagnetic and geoelectric field variations for Canada. Issue 7 (9th July 2016) - Nikitina, L.; Trichtchenko, L.; Boteler, D. H.
Abstract: Disturbances of the geomagnetic field produced by space weather events can have an impact on power systems and other critical infrastructure. To mitigate these risks it is important to determine the extreme values of geomagnetic activity that can occur. More than 40 years of 1 min magnetic data recorded at 13 Canadian geomagnetic observatories have been analyzed to evaluate extreme levels in geomagnetic and geoelectric activities in different locations of Canada. The hourly ranges of geomagnetic field variations and hourly maximum in rate of change of the magnetic variations have been used as measures of geomagnetic activity. Geoelectric activity is estimated by the hourly peak amplitude of the geoelectric fields calculated with the use of Earth resistivity models specified for different locations in Canada. A generalized extreme value distribution was applied to geomagnetic and geoelectric indices to evaluate extreme geomagnetic and geoelectric disturbances, which could happen once per 50 and once per 100 years with 99% confidence interval. Influence of geomagnetic latitude and Earth resistivity models on the results for the extreme geomagnetic and geoelectric activity is discussed. The extreme values provide criteria for assessing the vulnerability of power systems and other technology to geomagnetic activity for design or mitigation purposes. Key Points: Extreme value analysis for geomagnetic and geoelectric activities across Canada Extreme geomagnetic and geoelectric disturbances which could happen once in 50 and 100 years Results are useful to assess impact from space weather to power systems and other technology